HIGH SCHOOL STUDENT’S RESPONSE TOWARDS AUTHENTICCOLLABORATIVE ASSESSMENT MODEL BOOK OF POETRY WRITING - Suci Sundusiah; Ahmad Rofi'uddin; Heri Suwignyo; Imam Agus Basuki (Jurusan Sastra Indonesia, 2017)
The current research is a part of improvement research on authenticcollaborative assessment model book for High School. Book's arrangement was based on the problem that implementation on authentic assessment in poetry writing class at introduction study in three student groups collaboratively has not been well accomplished. Poetry writing learning aims at objective authentic assessment and involves student collaboratively. Tested unlimited and extensive student groups, the book is able to be accepted and applied as assessment model which improves learning result.